Use of the 5Qs model to assess and improve the quality of health services according to the modified Deming Technique (PDSA): An exploratory study of a sample of patients from Imam al-Kadhimin Medical City (Entrepreneurship Journal for Finance and Business, 2021)
This research aims to assess the quality of health services in Imam Al-Kazimin (peace be upon him) Medical City by diagnosing strengths and weaknesses using the (5Qs) model and improving them through the modified Deming technique (PDSA). The research sample was distributed to patients in the Medical City, and SPSS 23, v.25 was used to analyze the research data, and the results showed the possibility of evaluating the quality of health services in the Medical City. Using the 5Qs model, by determining the size of the gap for each of them after arranging the objective quality first, followed by the general feeling quality, then the quality of the process, then the quality of the infrastructure, then the reactive quality, in addition to the ability of the Modified Deming Technology (PDSA) to improve the quality of health service from Through the development of mechanisms and procedures for strengthening the strengths and addressing the Diagnosed Vulnerabilities Model (5Qs) according to the latest technological developments used in the health system.